2014
DOI: 10.1080/13803395.2014.943696
|View full text |Cite
|
Sign up to set email alerts
|

Effects of information processing speed on learning, memory, and executive functioning in people living with HIV/AIDS

Abstract: Introduction It is unclear whether or to what degree literacy, aging, and other neurologic abnormalities relate to cognitive deficits among people living with HIV/AIDS in the combined antiretroviral therapy (CART) era. The primary aim of this study was to simultaneously examine the association of age, HIV-associated motor abnormalities, major depressive disorder, and reading level with information processing speed, learning, memory, and executive functions, and to determine if processing speed mediated any of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 56 publications
4
36
0
1
Order By: Relevance
“…Cohen's d = .64, a 'medium' effect. These findings agree with those of Fellows et al (2014) who found that information processing skills in persons living with HIV were poorer for than controls who where HIV negative.…”
Section: Group Comparisonsupporting
confidence: 80%
“…Cohen's d = .64, a 'medium' effect. These findings agree with those of Fellows et al (2014) who found that information processing skills in persons living with HIV were poorer for than controls who where HIV negative.…”
Section: Group Comparisonsupporting
confidence: 80%
“…Researchers have also developed and utilized derived scores in an attempt to better isolate cognitive processes associated with TMT-B performance (Lamberty et al, 1994; Lange, Iverson, Zakrzewski, Ethel-King, & Franzen, 2005; Salthouse, 2011). The three most common methods are subtracting total time to complete TMT-A from total time to complete TMT-B (B–A); the ratio of B to A (B:A), or the residual of TMT-B after it has been regressed on Part A (BrA; Fellows, Byrd, & Morgello, 2014; Fellows & Schmitter-Edgecombe, 2015; Salthouse, 2011). In a principal components analysis, the BrA derived score loaded on the same component as CLOX (Royall, Cordes, & Polk, 1998) and the Behavioral Assessment of the Dysexecutive Syndrome Zoo map subtest (Wilson, Alderman, Burgess, Emslie, & Evans, 1996), which provides further support for this index as a measure of more complex executive functions (Fellows & Schmitter-Edgecombe, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for greater impairment in the coinfected patients may be the higher risk of neurotoxicity due to CNS insults by both viruses in fronto-striatal areas. Particularly, high levels of HIV have been found in the basal ganglia (notably the substantia nigra) and fronto-cortical areas (Kumar, Borodowsky, Fernandez, Gonzalez, & Kumar, 2007), and it has been shown that fronto-striatal neuronal circuitry mediates processing speed (e.g., Fellows, Byrd, & Morgello, 2014;Kumar, Ownby, Waldrop-Valverde, Fernandez, & Kumar, 2011;Salthouse, 1996). Additionally, there is evidence that fronto-striatal circuits are rich in dopaminergic activity and it is hypothesised that dopamine depletion exacerbates processing speed impairment in HIV (Kumar et al, 2011).…”
Section: Discussionmentioning
confidence: 96%